The Improvement of Skin Whitening of Phenylethyl Resorcinol by Nanostructured Lipid Carriers - Kim, Bo-Sik; Choi, Jae-Hwan; Kim, Inhye; Lee, Eunji; Kim, Sung-Yeon; Lee, Jae-Young; Cho, Cheong-Weon (Nanomaterials (Basel, Switzerland), 2017)
Phenylethyl resorcinol (4-(1-phenylethyl)1,3-benzenediol) (PR) is a new whitening agent that has been found to have the ability to inhibit tyrosinase activity. However, the application of PR is limited by photo instability and poor solubility. PR-loaded nanostructured lipid carriers (PR-NLCs) were prepared by the hot-melted ultrasonic method. Glycerol monostearate and olive oil were selected as the solid lipid and liquid lipid for considering the solubility of PR in liquid lipid and partition coefficient of PR in solid lipid, respectively. The particle size and polydispersity index of PR-NLCs were 57.9 ± 1.3 nm and 0.24 ± 0.01, respectively. The encapsulation efficiency and loading capacity of PR-NLCs were 93.1 ± 4.2% and 8.5 ± 0.4%, respectively. The stability test demonstrated that the incorporation of PR into NLCs conferred excellent physicochemical stability and photo stability for at least three months at 4 °C in the dark and 25 °C under daylight. In vitro release of PR-NLCs revealed a sustained release pattern. Cellular tyrosinase assay showed that PR-NLCs could significantly inhibit tyrosinase activity in melanoma cells, suggesting that NLCs can be used as a biocompatible nanocarrier for the effective delivery of skin whitening agents.